1988
DOI: 10.1111/j.1570-7458.1988.tb01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior of potato aphid affected by glandular trichomes of wild tomato

Abstract: Mortality of the potato aphid, Macrosiphum euphorbiae (Thomas), on Lycopersicon pennellii (Corr.) D'Arcy and its F1 hybrid with Lycopersicon esculentum Mill. was significantly greater than that on L. esculentum. Physical entrapment was not the sole mechanism of resistance in L. pennellii since few late instar aphids were found trapped in the sticky glandular exudate of the type IV trichomes; entrapment could, however, affect survival of early instars. Aphid settling on L. pennellii was dramatically less than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0
5

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 12 publications
9
63
0
5
Order By: Relevance
“…But neither of these authors observed any increased mortality of insects that could be associated with the toxicity of the sugar esters. Similar results were obtained by Goffreda et al (1988Goffreda et al ( , 1989 for GEs from glandular trichomes of Solanum pennellii Correll, which reduced feeding and survival of the green peach aphid and the potato aphid (Macrosiphum euphorbiae). The effect was possibly associated with both the physical entrapment of aphids and the deterrence of aphid settling.…”
Section: Introductionsupporting
confidence: 72%
“…But neither of these authors observed any increased mortality of insects that could be associated with the toxicity of the sugar esters. Similar results were obtained by Goffreda et al (1988Goffreda et al ( , 1989 for GEs from glandular trichomes of Solanum pennellii Correll, which reduced feeding and survival of the green peach aphid and the potato aphid (Macrosiphum euphorbiae). The effect was possibly associated with both the physical entrapment of aphids and the deterrence of aphid settling.…”
Section: Introductionsupporting
confidence: 72%
“…Glandular hairs are a common defensive feature of plants (11)(12)(13), where they have been shown to be effectively protective against insects (14). They are of less frequent occurrence in insects, but the chemistry of the secretion of insectan hairs, to the extent that it is known, can be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Slow turnover numbers for enzymes of the terpenoid pathway might also be a factor. It (25), tobacco (3), tomato (9), and several other species. For example, Goffreda et al (9) …”
Section: Is Exudate Accumulation Capacity Related To the Structure Ofmentioning
confidence: 99%